2018
DOI: 10.15420/aer.2018.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Arrhythmias in Pulmonary Hypertension: Pathogenesis, Prognosis and Management

Abstract: Atrial arrhythmias, including atrial fibrillation and atrial flutter, are common in patients with pulmonary hypertension and are closely associated with clinical decompensation and poor clinical outcomes. The mechanisms of arrhythmogenesis and subsequent clinical decompensation are reviewed. Practical implications and current evidence for the management of atrial arrhythmias in patients with pulmonary hypertension are summarised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(66 citation statements)
references
References 61 publications
0
58
1
7
Order By: Relevance
“…There are no randomized studies comparing rhythm versus rate control in PH patients with atrial arrhythmias. Typically PH has been excluded in clinical trials of atrial fibrillation [95]. Cannillo et al (2015) found that in patients with PAH, including a small representation of Group 3 PH, the presence of a supraventricular (atrial) tachycardia was associated with increased hospitalization and mortality [96].…”
Section: Atrial Arrhythmiasmentioning
confidence: 99%
“…There are no randomized studies comparing rhythm versus rate control in PH patients with atrial arrhythmias. Typically PH has been excluded in clinical trials of atrial fibrillation [95]. Cannillo et al (2015) found that in patients with PAH, including a small representation of Group 3 PH, the presence of a supraventricular (atrial) tachycardia was associated with increased hospitalization and mortality [96].…”
Section: Atrial Arrhythmiasmentioning
confidence: 99%
“…Цікаві дані патофізіологічного механізму розвитку ФП наводять B. Wanamaker та співавтори при хронічній легеневій гіпертензії, які поєднують цей механізм у так званий серцево-легеневий континуум, за яким хронічна легенева гіпертензія спричиняє підвищення тиску в правому передсерді та розтягування правого передсердя, що супроводжуються розвитком фіброзу, структурними порушеннями і, як наслідок, виникненням ФП [20].…”
Section: оригінальні дослідженняunclassified
“…Обстежено 125 пацієнтів, госпіталізованих із ГКС у центр проведення перкутанних коронарних втручань КНП Харківської обласної ради «Обласна клінічна лікарня», протягом чотирьох років у період 2015-2018 рр. Критерієм залучення в дослідження була наявність ГКС [5,6,20], критеріями вилучення -наявність тяжких супутніх захворювань (активні онкологічні процеси, хронічна ниркова недостатність IV ступеня тощо), вади серця, відмова пацієнта від участі в дослідженні.…”
Section: матеріали і методиunclassified
“…Предикторами НРС у пациентов с легочной гипертензией являются дилатация левого и правого желудочков, повышение давления в правом предсердии, увеличение содержания натрийуретических пептидов и билирубина, снижение сердечного выброса. Повышение давления в правом предсердии и связанное с этим структурное и электрофизиологическое ремоделирование миокарда предсердий -один из основных механизмов развития суправентрикулярных НРС наряду с гипоксией у этих больных [66]. Дисфункция автономной нервной системы с активацией ее симпатического звена также вносит существенный вклад в аритмогенез у пациентов данной категории [66].…”
Section: болезни органов дыханияunclassified
“…Повышение давления в правом предсердии и связанное с этим структурное и электрофизиологическое ремоделирование миокарда предсердий -один из основных механизмов развития суправентрикулярных НРС наряду с гипоксией у этих больных [66]. Дисфункция автономной нервной системы с активацией ее симпатического звена также вносит существенный вклад в аритмогенез у пациентов данной категории [66].…”
Section: болезни органов дыханияunclassified